Thoracic Sarcoma: A New Glance at the Epidemiological Characteristics of Disease in Iran from 2009 to 2014 - Hamide Rahmani Seraji; Mohmmad Esmaeil Akbari; Hamid Rezvani; Davood Bashash; Maryam Mabani; Atieh Akbari; Alireza Raeisi; Ghasem Janbabee; Sina Salari (Tehran University of Medical Sciences, 2022)
Background: The heterogeneity, high rate of mortality and lack of comprehensive diagnostic methods have categorized primary sarcomas of the thorax as a malignancy with dismal outcomes and unknown etiology. Given the fundamental role of epidemiological analysis in establishing management strategies, we designed a study with focus on the epidemiological characteristics of primary thoracic sarcomas in Iran.   Methods: This national population-based cancer study was conducted on patients with histologically confirmed sarcoma of the thorax referred to the Iranian National Cancer Registry between 2009 and 2014. The incidence was calculated as number of cases per 100,000 person-years and was age-adjusted by the direct method using the weight of the 1960 world standard population.   Results: Over a 6-year period, 1477 cases with pathologically confirmed thoracic sarcomas were registered in Iran, of which 896 were male and 581 were female. Khuzestan Province had the highest incidence of thoracic sarcomas as compared to other provinces. Malignant mesothelioma was the most common histological subtype (20.85%). Moreover, the age-standardized incidence rate (ASR) of the disease was 1.94 per 100,000 which was more common in males than females with the highest incidence rate in men aged more than 65 years.  Conclusion: Our study provided valuable epidemiologic data on characteristics of thoracic sarcomas. This data can be used for strategizing preventive measures.